2021
DOI: 10.1007/s10803-021-04878-0
|View full text |Cite
|
Sign up to set email alerts
|

Autism Detection in Children by Combined Use of Gaze Preference and the M-CHAT-R in a Resource-Scarce Setting

Abstract: Most children with autism spectrum disorder (ASD), in resource-limited settings (RLS), are diagnosed after the age of four. Our work confirmed and extended results of Pierce that eye tracking could discriminate between typically developing (TD) children and those with ASD. We demonstrated the initial 15 s was at least as discriminating as the entire video. We evaluated the GP-MCHAT-R, which combines the first 15 s of manually-coded gaze preference (GP) video with M-CHAT-R results on 73 TD children and 28 child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…The Autism Diagnostic Observation Schedule ñ Second Edition (ADOS-2), an empirically supported observational assessment tool that can be used to determine the presence and severity of ASD, is another commonly used early detection tool (Marschall, Piehl, & Bernat, 2018). However, the use of ADOS-2 cannot be done by just anyone; it must be done by trained clinical personnel (Rescorla et al, 2019;Jensen et al, 2021). Besides that, The Autism Diagnostic InterviewñRevised (ADI-R), a standard interview used in research and clinical diagnostic evaluation when ASD is suspected, is the most widely used and evidencesupported report on interview results with caregivers used to detect ASD (Rutter, Le Couter, & Lord, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Autism Diagnostic Observation Schedule ñ Second Edition (ADOS-2), an empirically supported observational assessment tool that can be used to determine the presence and severity of ASD, is another commonly used early detection tool (Marschall, Piehl, & Bernat, 2018). However, the use of ADOS-2 cannot be done by just anyone; it must be done by trained clinical personnel (Rescorla et al, 2019;Jensen et al, 2021). Besides that, The Autism Diagnostic InterviewñRevised (ADI-R), a standard interview used in research and clinical diagnostic evaluation when ASD is suspected, is the most widely used and evidencesupported report on interview results with caregivers used to detect ASD (Rutter, Le Couter, & Lord, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Janvier et al (2019) present a visual-based Muhammad Cahyadi,Thalsa Syahda Aqilah,Ediyanto Ediyanto and Ahsan Romadlon Junaidi 20 screening tool to eliminate the need for high literacy skills in parents of ASD children, thanks to ADOS-2, which is considered weak for detecting ASD in children whose parents have low educational and economic conditions. Therefore, Jensen et al (2021) found that combining Gaze Preference with M-CHAT-R can help screen children with ASD in an environment with limited resources. Due to possible cultural differences, the use of screening and diagnostic tools in different countries necessitates further consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Entre las nuevas herramientas de diagnóstico tenemos la publicada en el estudio de Jensen et al, en colaboración con el Grupo de Estudio del Autismo en el Perú (26), titulado "Detección de autismo en niños mediante el uso combinado de la preferencia de mirada y el M-CHAT-R (GP-M-CHAT/R) en entornos de escasos recursos" realizado en niños peruanos de 36 a 99 meses. Se les presentaron videos de un minuto de exposición, con escenas abstractas a la derecha de la pantalla y escenas sociales a la izquierda, demostrando que la preferencia visual, tanto el enfoque social como el tiempo de distracción, sirven como marcadores para detectar el riesgo del TEA en los niños.…”
Section: Rev Neuropsiquiatr 2021; 84(3): 175-182unclassified
“…Las diferencias son detectables en tan solo quince segundos de preferencia de mirada. Esta prueba asociada al M-CHAT/R mejora el grado de confiabilidad, de sensibilidad y especificidad para detección temprana del TEA en poblaciones con recursos limitados (26).…”
Section: Rev Neuropsiquiatr 2021; 84(3): 175-182unclassified